AC/DC Superimposed Breakdown Characteristics and Electric Field Simulation Analysis of Oil-Paper Insulation in Converter Transformers - Huang, Xiaofan; Yan, Jun; Pan, Aiqiang; Zhang, Yufan (EAI Endorsed Transactions on Energy Web, 2026)
This study investigates the electric field distribution and breakdown characteristics of oil-paper insulation in a 500 kV converter transformer under AC/DC superimposed voltages. The electric field distribution within the winding end insulation structure at the valve side was analyzed under various voltage conditions using finite element simulations. Experiments were conducted on insulating oil and oil-paper samples to measure their breakdown strengths under different AC/DC components. The results reveal that under DC voltage, the electric field concentrates inside the insulation paper, whereas under AC voltage, it is mainly distributed across the oil gap. Under AC/DC superimposed voltages, a decreasing AC ratio shifts the electric field from the oil gap to the insulation paper and increases the maximum electric field strength. As the DC component rises, the breakdown strength of both oil and oil-paper samples first decreases and then increases, with oil-paper insulation consistently exhibiting higher strength. These findings indicate that although oil-paper insulation can withstand higher electric fields and thus ensure transformer safety, low DC components may increase the risk of oil discharge or failure. Therefore, the design of next-generation high-voltage converter transformers must account for oil-paper insulation degradation under low DC ratios, and effective mitigation strategies—such as controlling the internal electric field or enhancing dielectric strength—are essential for ensuring reliability under AC/DC superimposed voltages.
Keywords: Oil-Paper Insulation; AC/DC Superimposed Voltage; Finite Element Method; Electric Field; Breakdown Strength